The Influence of Perceived Usefulness, Perceived Ease of Use and Perceived Risk on Continuance Intention at E-Wallet DANA in Bandung - Mila Popi Purnama; Devilia Sari (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Electronic wallets exist because of the fast-paced changes in people's lifestyles. However, some users are still worried about the big consequences, for example the reliability and security of the e-wallet. DANA is an e-wallet with >100 million users throughout Indonesia. With so many users, there is a need for an adequate security system. The operation of the technology should not require much effort. However, there are reviews that the DANA e-wallet still finds difficulties and there is a gap (gap) between perceived benefits, ease of use and perceived risk. The risk of using an e-wallet can affect the user experience and become a barrier to continued use. This study aims to see the existence of "The Influence of Perceived Benefits, Perceived Ease of Use and Perception of Risk on Continuance Intention in DANA e-Wallet in Bandung City ''. The methodology in the research carried out by the researcher is quantitative using a causal descriptive approach, multiple linear regression analysis is used as a technique that is tested through SPSS 25 software. The number of samples used by the researcher is 190 people. The results of the research show that the variables of perceived benefit, perceived ease of use and perceived risk have a positive and significant effect on the variable continuity intention either partially or simultaneously. The influence of the independent variable is 30.2% and the other (100%-30.2%) = 69.8% is the influence of other variables outside of this research.